High Inter-muscular Fat Is Associated with Poor Mobility Function in Older Adults, Only When Accompanied by Low Muscle Area (P01-026-19). (13th June 2019) - Farsijani, Samaneh; Santanasto, Adam; Cawthon, Peggy; Boudreau, Robert; Goodpaster, Bret; Kritchevsky, Stephen; Harris, Tamara; Newman, Anne
Abstract: Objectives: To determine whether the associations between thigh inter-muscular-fat area, anthropometric characteristics and physical performance varies in old adults with low vs. high thigh muscle cross-sectional area. Methods: Cross-sectional analysis of year 6 data from 1903 participants (52.2% women) of the Health ABC study aged 74–85y. Mid-thigh muscle composition (by CT), body composition (DXA) and physical performance were compared across quartiles of mid-thigh inter-muscular fat area. General linear model univariate analysis was used to study the associations between inter-muscular fat area and physical function according to low or high mid-thigh muscle cross-sectional area (using the 50th percentile). Results: In participants with low mid-thigh muscle area, there was a threshold effect in which high inter-muscular fat was related to poor mobility function after the 2nd quartile (>23.7 cm 2 in men and >21.3 cm 2 in women). While, in participants with high mid-thigh muscle area, high inter-muscular fat was not associated with poor mobility function. Inter-muscular fat had no significant association with isokinetic knee strength in participants with either low or high muscle area. However, across all inter-muscular fat conditions, participants with low muscle area had lower leg strength than those with high muscle area. Conclusions: The negative effects of inter-muscular fat in aging are greatly influenced by the presence of concurrent low muscle mass. Funding Sources: NIA/NIH.